Sosialisasi UU ITE kepada Masyarakat Kelurahan Bumi Laweyan Surakarta - Kusumo, Bambang Ali; Putri, Kartika Asmanda; Broto Laksito, FX Hastowo (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The enactment of Law No. 1 of 2024, as the second amendment to Law No. 11 of 2008 concerning Information and Electronic Transactions, holds paramount significance for both society and the state. Public dissemination becomes essential to ensure community members comprehend and adhere to these regulations. The law serves to guide citizens in understanding and implementing its provisions. Information exchange and communication among community members fulfill fundamental human needs and constitute basic human rights. From the state's perspective, this law establishes guidelines for conducting information and electronic transactions, preventing misuse and deviation in information reception and electronic transactions. In today's globalized era, information and electronic transactions have become essential human necessities. Thus, communities must develop legal awareness for compliance. For those who violate these provisions, enforcement mechanisms through criminal sanctions are established under this law.